Chemokine CXCL9, a marker of inflammaging, is associated with changes of muscle strength and mortality in older men - Seo, Da Hea; Corr, Maripat; Patel, Sheena; Lui, Li-Yung; Cauley, Jane A.; Evans, Daniel; Mau, Theresa; Lane, Nancy E. (Osteoporosis international, 2024)
Summary Our study examined associations of the CXC motif chemokine ligand 9 (CXCL9), a pro-inflammatory protein implicated in age-related inflammation, with musculoskeletal function in elderly men. We found in certain outcomes both cross-sectional and longitudinal significant associations of CXCL9 with poorer musculoskeletal function and increased mortality in older men. This requires further investigation. Purpose We aim to determine the relationship of (CXCL9), a pro-inflammatory protein implicated in age-related inflammation, with both cross-sectional and longitudinal musculoskeletal outcomes and mortality in older men. Methods A random sample from the Osteoporotic Fractures in Men (MrOS) Study cohort ( N = 300) was chosen for study subjects that had attended the third and fourth clinic visits, and data was available for major musculoskeletal outcomes (6 m walking speed, chair stands), hip bone mineral density (BMD), major osteoporotic fracture, mortality, and serum inflammatory markers. Serum levels of CXCL9 were measured by ELISA, and the associations with musculoskeletal outcomes were assessed by linear regression and fractures and mortality with Cox proportional hazards models. Results The mean CXCL9 level of study participants (79.1 ± 5.3 years) was 196.9 ± 135.2 pg/ml. There were significant differences for 6 m walking speed, chair stands, physical activity scores, and history of falls in the past year across the quartiles of CXCL9. However, higher CXCL9 was only significantly associated with changes in chair stands ( β =  − 1.098, p < 0.001) even after adjustment for multiple covariates. No significant associations were observed between CXCL9 and major osteoporotic fracture or hip BMD changes. The risk of mortality increased with increasing CXCL9 (hazard ratio quartile (Q)4 vs Q1 1.98, 95% confidence interval 1.25–3.14; p for trend < 0.001). Conclusions Greater serum levels of CXCL9 were significantly associated with a decline in chair stands and increased mortality. Additional studies with a larger sample size are needed to confirm our findings.